Framework for measuring process innovation performance at indonesian state-owned companies - Patdono Suwignjo; I Ketut Gunarta; Naning Aranti Wessiani; Andhika Eko Prasetyo; Lila Yuwana (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Several state-owned companies (SOEs) have successfully implemented process innovation. This paper examines the success factors that influence the successful implementation of process innovation in Indonesian state-owned companies. The present study used the three stages of an online questionnaire in the Delphi method to obtain consensus from experts. The consensus was measured based on the mean and standard deviation of the assessment answers provided by our respondents. Based on the development of process innovation implementation frameworks shown in previous studies, we obtained 28 factors that influence the successful implementation of process innovation. Our panelists believed that human resources and organizational factors, such as leadership, problem understanding, strategy, and culture, affected the success of process innovation in SOEs, even more than the research and development budget, support, and commitment factor of a given company. Meanwhile, cost efficiency was the main factor driving a company's motivation to implement process innovation. The success factors in implementing process innovation are an essential consideration for the management of other SOEs eager to improve their company's innovation performance, especially process innovation. Success factors were carried out comprehensively for all implementation indicators of process innovation, including inputs, process (idea generation, idea selection, and idea implementation), outputs and outcomes, diffusion, culture, strategies, and push and pull factors.
Keywords: 650; Delphi method; process innovation; state-owned enterprises; success factors